The Saga of Pandemics through the Literary Lens - Sen, Nandini C; Chawla, Abhay (Utan Kayu Publishing, 2023)
Disease, illness and death have been a human being’s constant companion right from the dawn of civilization and Pandemics are a part of this fatal manifestation which has been witnessed century upon century, successfully wreaking havoc upon the unsuspecting mankind. A pandemic (from Greek - pan, meaning